2005
DOI: 10.1002/ijc.21563
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between genetic alterations and prognosis in sporadic colorectal cancer

Abstract: Because chromosomal chromosomal instability (CIN) and microsatellite instability (MSI) are important genetic alterations in colorectal cancers, we classified the sporadic colorectal cancers (CRC) on the status of the CIN and MSI and explored their molecular profiles. A total of 213 colorectal tumors were collected for analysis of DNA ploidy, MSI, loss of heterozygosity (LOH), mutation of p53 (exons 5 to 9), Ki-ras (exons 1 and 2) and BRAF (V599E). Relationships between clinicopathological variables and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 41 publications
(48 reference statements)
8
47
2
4
Order By: Relevance
“…Several studies have reported a link between somatic mutations in components of the EGFR-RAS-RAF pathway and evidence of mucinous differentiation in colorectal carcinomas, [59][60][61][62][63] but the inclusion of microsatelliteunstable carcinomas in many of these studies is likely to have confounded the association because of previous observations that microsatellite-unstable tumors are associated with overexpression of MUC2 and MUC5AC 19 and a mucinous phenotype. 11,12,64 KRAS mutations have been identified in 65% of mucinous colorectal carcinoma, 65 and associations between mutations in the EGFR-RAS-RAF pathway and other types of malignancy have been made, 66 including mucinous ovarian cancers, half or more of which possess somatic KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a link between somatic mutations in components of the EGFR-RAS-RAF pathway and evidence of mucinous differentiation in colorectal carcinomas, [59][60][61][62][63] but the inclusion of microsatelliteunstable carcinomas in many of these studies is likely to have confounded the association because of previous observations that microsatellite-unstable tumors are associated with overexpression of MUC2 and MUC5AC 19 and a mucinous phenotype. 11,12,64 KRAS mutations have been identified in 65% of mucinous colorectal carcinoma, 65 and associations between mutations in the EGFR-RAS-RAF pathway and other types of malignancy have been made, 66 including mucinous ovarian cancers, half or more of which possess somatic KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that MSI is significantly related to improved prognosis independent of the other prognostic factors such as the stage and site of the tumor. The mortality is decreased in MSI+ patients (19)(20)(21). Many studies have found that Lynch patients have a more favorable prognosis than MSI+ patients with sporadic CRC (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality is decreased in MSI+ patients (19)(20)(21). Many studies have found that Lynch patients have a more favorable prognosis than MSI+ patients with sporadic CRC (21)(22)(23). The MSI status is also related to sensitivity to the chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 mutation is not likely to have caused elevated MS mutation rates because mutations in P53 have been shown to be unassociated with MS instability in a variety of human cancers such as prostate (33), gastric (34), and esophageal (35) carcinomas. In human colorectal cancer, mutations in P53 have been shown to be inversely correlated with MS instability (36)(37)(38). However, this negative correlation is not likely to be due to decreased MS mutation rates in tumors with P53 mutations but, rather, is likely to reflect the fact that in colorectal cancer, mutations in TP53 and in MMR genes represent two independent pathways to cancer pathogenesis (i.e., the ''chromosomal instability'' versus the ''microsatellite instability'' pathways; ref.…”
Section: Discussionmentioning
confidence: 99%